Intervention program for reduction of overweight and obesity among 11- to 15- year old school children in District 1 of Shiraz, Iran - Rahnama, Rozina (2015)
Childhood obesity is one of the most serious public health challenges of the 21st century. The problem is global and is steadily affecting many low- and middle-income countries, particularly in urban settings. In Iran, the overall prevalence of overweight has increased from 10.4% during 2000 to 2004 to 10.8% during 2005 to 2010. The aim of this cluster randomized controlled trial study was to evaluate the impact of an intervention program on BMI, physical activity, diet knowledge and diet behavior for reduction of overweight and obesity among students aged 11-15 years in district 1 of Shiraz/Iran. Multistage cluster sampling method was used for selection of the sample. Out of 64 schools in District 1 of Shiraz, eight schools randomly selected and assigned to intervention and control group. A self-administered validated questionnaire was used to measure socio-demographic, BMI, physical activity, diet knowledge and diet behavior of the respondents. An educational module adapted based on World Health Organization Guideline for obesity and overweight prevention and delivered by researcher to the intervention groups during one month. Four-hour integrated obesity and overweight prevention program comprising of four structured modules was developed. While, the control group was exposed to normal school program. Descriptive and multivariate statistics were used for analyzing the data using IBM, SPSS version 21. A mixed design repeated measure ANOVA (Generalized Estimating Equation) considering cluster effect and Cohen’s range band on effect size (ES) were applied to assess the impact of the intervention. The outcome measures were assessed at baseline and 6 months postintervention. Data were collected from 2040 students aged 11-15 years that 1040 respondents randomized to the intervention group and 1000 respondents to the control group. The response rate for the intervention group was 97.8% and for the control group was 96.4%. Out of 2040 respondents, 52.1% were male and the majority were Moslem 98.2%. Respondents in the intervention arm after controlling for cluster effect showed significant improvements in BMI (p=0.003), diet behavior (p<0.001) and diet knowledge (p<0.001) while the physical activity had no improvements (p=0.804). In conclusion, the developed intervention program related to obesity and overweight prevention was more effective in improving BMI, diet behavior and diet knowledge among Iranian students aged 11-15 years, while it was not effective in increasing physical activity scores. Future school-based interventional research related to prevention of obesity and overweight should be used mixed methodologies while study peer influence among adolescents.